Kinetika Pertumbuhan dan Analisis Fourier Transform Infra Red (FTIR) Spectroscopy Bakteri Penghasil Pigmen Serratia marcescens dan Rhodococcus sp. - Kusdiyantini, Endang (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2021)
Serratia marcescens and Rhodococcus sp. are two pigment-producing bacteria that have the potential to be used in industry. Pigment production is closely related to bacterial growth. This study examined the growth and specific growth rate (umaks) as well as functional group analysis using FTIR from the bacteria S. marcescens and Rhodococcus sp. isolated from the Gedong Songo hot spring, Bandungan Semarang. The results showed that the maximum growth of S. marcescens and Rhodococcus sp. of 0.044 g/L and 0.0038 g/L were achieved at the same hour, namely 48 hours of incubation time. The specific growth rate (umax) of S. marcescens was 0.11(1/hour) and Rhodococcus sp. of 0.15 (1/hour). FTIR analysis of these two bacteria showed absorption at N-H, C-H, O-H and C=O, so that the pigment compounds belonged to the alkaloid group.